2015
DOI: 10.1155/2015/752194
|View full text |Cite
|
Sign up to set email alerts
|

Application of Acupoints and Meridians for the Treatment of Primary Dysmenorrhea: A Data Mining-Based Literature Study

Abstract: Background. Dysmenorrhea is a common problem for which acupuncture provides effective analgesia. Although acupoint selection affects the effectiveness of acupuncture, the basic rules of acupoint selection are little understood. This study aims to investigate the principles of acupoint selection and characteristics of acupoints used for primary dysmenorrhea. Methods. PubMed, China National Knowledge Infrastructure, and Chinese Biomedical Database were searched for clinical trials published in English or Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 17 publications
1
34
0
2
Order By: Relevance
“…Sanyinjiao (SP6), located medially four-finger wide above the ankle, has been the major acupoint to be used for treating PD since ancient times according to the meridian theory of Chinese acupuncture. Further, it is used most frequently in treating PD according to our previous data mining analysis from literature [ 48 ]. In addition, recent RCTs have shown that SP6 stimulation could relieve the abdominal pain and improve the menstrual pain-related symptoms [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sanyinjiao (SP6), located medially four-finger wide above the ankle, has been the major acupoint to be used for treating PD since ancient times according to the meridian theory of Chinese acupuncture. Further, it is used most frequently in treating PD according to our previous data mining analysis from literature [ 48 ]. In addition, recent RCTs have shown that SP6 stimulation could relieve the abdominal pain and improve the menstrual pain-related symptoms [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the moxibustion group, two different TCM patterns of acupoints are selected for treatments (including diagnostic pattern 1: Qi-stagnation and blood stasis, and diagnostic pattern 2: congealing cold-camp). The acupoints for moxibustion treatment was based on data mining [ 27 , 28 ] from literature and expert opinions. Guanyuan (CV4), Shenque (CV8), and Sanyinjiao (SP6) were selected as key acupoints receiving moxa heat stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Among the alternative approaches, GBH, also known as Guizhi-Fuling-Wan (pill), is a widely used remedy for PD and has been employed since ancient times in East Asia. 13 21 22 GBH was first prescribed in the Essential prescriptions from the golden cabinet (Jin Gui Yao Lue) by Zhang Zhongjing of the Han Dynasty (206 bc –220ad). 23 The five ingredients of GBH are ramulus cinnamomi cassiae, sclerotium poriae cocos, cortex moutan radicis, semen pruni persicae and radix paeoniae lactiflorae, and these ingredients are combined in a ratio of 1:1:1:1:1.…”
Section: Discussionmentioning
confidence: 99%